Sacral Neuromodulation Outcomes in Male Patients with Chronic Urinary Retention. Issue 4 (5th February 2015) - Saber‐Khalaf, Mohammed; Abtahi, Bahareh; Gonzales, Gwen; Helal, Mohamed; Elneil, Sohier
<x xml:space="preserve">Abstract</x> Objectives To assess the outcome of two‐stage sacral neuromodulation (SNM) in men with chronic urinary retention (CUR) and factors affecting the response. Material and Methods Data were collected from 21 male patients with complete or partial CUR who underwent two‐stage SNM between 2006 and 2014. The implanted lead was connected to a temporary battery (stage‐1) and they were assessed over a period of 3–12 weeks. Those who had a residual volume of ≤100 mL, had an implantable pulse generator sited (stage‐2). Patients were followed up at 3 and 6 months initially, and 12 monthly thereafter. The following parameters were analyzed: age, onset of symptoms, precipitant causes for CUR, type of retention, associated voiding dysfunction and opiate intake. Results Surgery was the main precipitating cause of CUR in 5 (24%) patients. Stage‐1 SNM restored complete efficient voiding in 14 patients (66.7%) out of the 21 patients. The only parameter studied that showed a positive correlation with a successful outcome to SNM was the age of the patient, with a higher success rate in younger males (median age 37 years [p = 0.025]). There was no other significant finding when looking at other parameters studied. Stage‐2 was carried out in 13 out of 14 successful stage‐1 patients. SNM restored complete voiding or improved bladder emptying in all patients implanted with a battery, and this was sustained until the battery needed to be replaced with a mean follow up of 34 ± 23.7 months except in two cases that had removal after traumatic accidents. Conclusion Stage‐1 SNM was successful in 66.7% of male patients with CUR. Once stage‐2 was performed, successful voiding was maintained until the battery needed to be replaced. SNM success was better in men under a median age of 43 years. Further studies are encouraged to study this group of patients.